Advances in Pancreatic Cancer, Intraductal Papillary Mucinous Neoplasms, and Pancreatitis - Vege, Santhi Swaroop (Gastroenterology, 2018)
According to the theme of the Golden Jubilee Issue of our journal, we present a commentary on landmark contributions reported in the journal on pancreatic cancer, pancreatic cysts, and intraductal papillary mucinous neoplasms (IPMN) and pancreatitis.